2016
DOI: 10.1016/j.psyneuen.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid mediated regulation of inflammation in human monocytes is associated with depressive mood and obesity

Abstract: Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis is observed in various conditions, including depression and obesity, which are also often related. Glucocorticoid (GC) resistance and desensitization of peripheral GC receptors (GRs) are often the case in HPA dysregulation seen in depression, and GC plays a critical role in regulation of inflammation. Given the growing evidence that inflammation is a central feature of some depression cases and obesity, we aimed to investigate the immune-regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…However, our study revealed that the higher levels of cortisol found in the obese group have no effect in acetylation-deacetylation events in PBMC of obese individuals. In fact, the immunosuppressive action of cortisol in LPS-stimulated monocytic production of TNF- α was inhibited in obese subjects [ 41 ]. Thus, the impaired cortisol action on PBMC of obese individuals may contribute to the enhancement in proinflammatory cytokine production and histone H4 hyperacetylation in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study revealed that the higher levels of cortisol found in the obese group have no effect in acetylation-deacetylation events in PBMC of obese individuals. In fact, the immunosuppressive action of cortisol in LPS-stimulated monocytic production of TNF- α was inhibited in obese subjects [ 41 ]. Thus, the impaired cortisol action on PBMC of obese individuals may contribute to the enhancement in proinflammatory cytokine production and histone H4 hyperacetylation in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results extend previous findings to a more representative cohort of adults with obesity not awaiting bariatric surgery but at high CVD risk. The abolishment of the relation between CRP and depression after adjusting for BMI suggests that obesity and depression might share overlapping pathways of inflammatory activation , whereas anxiety modulates inflammation in persons with obesity at least partly through mechanisms independent of adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Greater NFκB DNA-binding concurrent with blunted glucocorticoid sensitivity has been reported in women with childhood abuse-related post-traumatic stress disorder (PTSD) (Pace, Wingenfeld et al 2012). Diminished suppression of inflammation by cortisol in monocytes was associated with increased depressive mood in patients (Cheng, Dimitrov et al 2016). Conversely, cognitive-behavioral stress management has been found to reverse anxiety-related upregulation of pro-inflammatory transcripts in leukocytes of women undergoing breast cancer treatment (Antoni, Lutgendorf et al 2012).…”
Section: Hallmarks Of Gr- Nfκb Dysfunction?mentioning
confidence: 99%